Аустријска библиотека у Београду - Џидић, Шејла (Инфотека - часопис за дигиталну хуманистику, 2026)
The paper examines the role of the Austrian Library in Belgrade as a contemporary cultural and educational institution whose impact goes beyond traditional library functions. Special emphasis is placed on the library’s programmatic activities – literary events, workshops, exhibitions, film screenings, and language development programs – which actively engage the public and promote contemporary Austrian culture. Furthermore, these programs contribute to the development of reading literacy, critical thinking, and lifelong learning, while simultaneously creating an open and safe space that fosters cultural growth, intercultural dialogue, creativity, and the connection of diverse social and cultural groups. The analysis of these activities demonstrates that the Austrian Library functions as a vibrant cultural hub that contributes to community development and strengthens cultural ties between Serbia and Austria. Keywords: Austrian Library in Belgrade, cultural and educational programs, cultural growth, lifelong learning, intercultural dialogue.